An international cross-sectional survey of antimicrobial stewardship programmes in hospitals. (18th December 2014) - Howard, P.; Pulcini, C.; Levy Hara, G.; West, R. M.; Gould, I. M.; Harbarth, S.; Nathwani, D.
Abstract: Objectives: To report the extent and components of global efforts in antimicrobial stewardship (AMS) in hospitals. Methods: An Internet-based survey comprising 43 questions was disseminated worldwide in 2012. Results: Responses were received from 660 hospitals in 67 countries: Africa, 44; Asia, 50; Europe, 361; North America, 72; Oceania, 30; and South and Central America, 103. National AMS standards existed in 52% of countries, 4% were planning them and 58% had an AMS programme. The main barriers to implementing AMS programmes were perceived to be a lack of funding or personnel, a lack of information technology and prescriber opposition. In hospitals with an existing AMS programme, AMS rounds existed in 64%; 81% restricted antimicrobials (carbapenems, 74.3%; quinolones, 64%; and cephalosporins, 58%); and 85% reported antimicrobial usage, with 55% linking data to resistance rates and 49% linking data to infection rates. Only 20% had electronic prescribing for all patients. A total of 89% of programmes educated their medical, nursing and pharmacy staff on AMS. Of the hospitals, 38% had formally reviewed their AMS programme: reductions were reported by 96% of hospitals for inappropriate prescribing, 86% for broad-spectrum antibiotic use, 80% for expenditure, 71% for healthcare-acquired infections, 65% for length of stay or mortality and 58% for bacterial resistance. Conclusions: The worldwide development and implementation of AMS programmes varies considerably. Our results should inform and encourage the further evaluation of this with a view to promoting a worldwide stewardship framework. The prospective measurement of well-defined outcomes of the impact of these programmes remains a significant challenge.